Impact of technological innovation and executive incentives on corporate financial performance in Western China - Li, Xiaona; Isa, Filzah Md; Kang, Ryan Ho Ming; Cheng, Peng (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the impact of technological innovation and executive incentives on corporate financial performance, with a particular focus on enterprises in Western China, an area often overlooked in existing research. It also addresses the lack of investigation into the interactive effects between these two factors. Using data from enterprises in Western China, Pearson correlation analysis is first conducted to examine preliminary correlations among variables. Subsequently, a multi-path structural equation modeling (SEM) is built to test both direct and moderating effects. Results indicate that technological innovation and salary-based incentives significantly enhance corporate financial performance, while equity incentives show insignificant or even negative moderating effects. Moreover, the effectiveness of executive incentives varies regionally, reflecting unique contextual characteristics of Western Chinese enterprises. These findings contribute to a deeper understanding of how innovation and incentive mechanisms function in underdeveloped regions. Practically, they provide insights for enterprises and policymakers seeking to design effective incentive structures and promote sustainable economic growth in Western China.